Layoffs and Their Ethical Implications under Scientific Management, Quality Management and Open-Book Management - Kidwell, Roland E. (Journal of business ethics, 2001)
Two major management philosophies of the 20th Century, scientific management and quality management, are often contrasted. Scientific management is seen as a system that focuses on task efficiencies whereas quality management is described as a collaborative, people-centered process approach to continuous improvement. This paper examines the ethical implications of these diverse approaches, particularly in the way information is used to decide which employees to lay off in times of economic difficulty. The paper uses case examples of quality management as teaching tools to place the conduct of managers within utilitarian, deontological and justice approaches to ethical decision making. Finally, it suggests that a third system, open-book management, may help deal with this ethical dilemma, though not without risk.